AN INTERACTION BETWEEN BOARD ATTRIBUTES AND EARNINGS MANAGEMENT OF LISTED MANUFACTURING COMPANIES IN NIGERIA - Jamiu Adeniyi, Akindele; Asri, Marsidi; Taophic Olarewaju, Bakare; Almustapha, Alhaji Aliyu (UNIMAS Publisher, 2023)
The study investigated an interplay between board attribute and earnings management of listed manufacturing companies in Nigeria. This study tested some board attributes indicators (audit fee, board independence, and board size), and earnings management was proxied using discretionary accruals using a sample of forty-two (42) manufacturing companies listed on Nigerian Exchange Group while purposeful sampling techniques were used to sampled from the population, covering the study period from 2010 to 2021. The data were analyzed using the Generalized method of moment by the use of E-View 12 econometric software and multivariate- regression model. The findings of the study show that there is a positive and statistically insignificant relationship between audit fees and earnings management. The study therefore concludes that a positive and statistical relationship exists between board attributes and earnings management of listed manufacturing companies in Nigeria. The study consequently recommends that ethical standards should be encouraged by the regulatory agencies if not mandated.